Analisis Konsep Diri pada Anak Tunggal di Kecamatan Ciracas - Alifia Farlina Safira; Fatma Nofriza (Journal on Education, 2024)
The position of children in the family is still an interesting phenomenon to research. One of them is an only child. The mere presence of children results in parents treating children with various parenting patterns and styles which ultimately affect the child's self-concept. This research aims to determine the self-concept that is formed in only children in Ciracas District, East Jakarta. This research approach is descriptive qualitative, namely field research using the case study method. The subjects of this research consisted of two students who were only children and were active students at a private university. Data collection tools used were observation, interviews and documentation. Data were analyzed through four steps, namely: data collection, data reduction, data presentation, and drawing conclusions. The research results found that the two students had different self-concepts. The first subject has a positive self-concept based on the characteristics, namely being able to accept oneself, be confident, have a positive attitude, not think negatively of others, carry out self-evaluation. The second subject has a negative self-concept based on the characteristics, namely not being able to accept oneself, still lacking self-confidence, having negative thoughts about other people, being easily angry, not liking oneself enough.